History of Islamic Education in Indonesia - Lumanatul Latifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The history of Islamic education in Indonesia has undergone significant development along with the evolution of the national education system. The first Islamic education in Indonesia usually took place in Islamic boarding schools, which are traditional Islamic schools that focus on teaching the Quran and hadith. These pesantrens became the center for the development and spread of Islam in various parts of Indonesia. After Indonesia's independence in 1945, the Indonesian government committed to creating a national education system that covered all aspects of life. This included Islamic education, which is recognized as one of the majority religions in Indonesia. The government integrated Islamic education into the national education system by giving recognition and support to madrasahs (Islamic schools) as well as developing a curriculum that included aspects of Islam. Renewal in Islamic education thought and religious moderation have become an integral part of Islamic education in Indonesia. This effort aims to ensure that Islamic education not only fulfills religious needs, but also contributes to the formation of citizens who hold moderate views, are tolerant, and open to various religious views. This research uses the historical study method to examine the history of Islamic education in Indonesia. The researcher conducted a historical study of various sources, such as books, journals, educational reports, and documentation.